Benefits of using combined oral contraceptive with drospirenone in 24+4 overweight adolescents - I V Kuznetsova; P A Nabiyeva (IP Berlin A.V., 2014)
Combined oral contraception is known as a reliable method of birth control that can provide additional benefits to health and quality of life . Reliability and the main characteristics of combined oral contraceptives do not differ significantly. At the same time, there is a group of women with special medical needs who have questions when choosing hormonal medications, safety and additional benefits issues should be treated with special care. Among these potential users with special needs, no doubt, are teenagers , and among the various problems that reduce the commitment of contraception - the likely problem of weight gain stands out. Given the propensity for uncontrolled weight gain , due to inherent physiological insulin resistance of puberty period , it is necessary to use drugs with optimal metabolic profile for the girls who are prone to being overweight or already are overweight . Among these medications the combinations containing drospirenone and ethinyl estradiol microdozes can be found.